Dahlia merckii and D. rupicola (Asteraceae, Coreopsideae), two new records for the Nueva Galicia region, Mexico - Macías Flores, Rafael Guadalupe; Ramírez Díaz, Claudia Janeth; González Gallegos, Jesús Guadalupe; Carrillo Reyes, Pablo; Castro Castro, Arturo (Instituto de Ecología, A.C., 2018)
Background and Aims: Dahlia is a characteristic genus of Asteraceae tribe Coreopsideae and eight species were known in Nueva Galicia. The objective of the present communication is to report two additional species.Methods: Botanical explorations were carried out in Nueva Galicia. Additionally, Dahlia specimens deposited at the herbaria ANSM, BUAP, CFNL, CHAPA, CIIDIR, ENCB, FCME, IBUG, IEB, MEXU, QMEX, SLPM, UAT, UAZ and XAL were reviewed and identified. Morphological descriptions and an identification key were made based on the analysis of specialized literature, revision of herbaria specimens and plants in the field. A database was compiled with the information and was analyzed with a geographic information system for the elaboration of distribution maps and proposals for protection categories.Key results: We documented Dahlia merckii and D. rupicola in Nueva Galicia. These new records extend the distribution area for both species to western Mexico. According to the categories and criteria of the International Union for Conservation of Nature, D. merckii can be qualified as a Least Concern species. Meanwhile, D. rupicola could be considered as Endangered if the area of occupation and the extension of occurrence are taken into account.Conclusions: This information extends the adaptive amplitude of both Dahlia species to habitats with different ecological conditions to those previously documented. We recommend carrying out studies to evaluate the conservation status of all the species in the genus according to conservation categories at national and international scales. Finally, the expanded distributions of D. merckii and D. rupicola indicate the need to continue and promote botanical exploration in Mexico.